THE EFFECTIVENESS OF ORANGE PEEL EXTRACT TOOTHPASTE IN LIGHTENING TEETH AND PREVENTING BACTERIAL INFECTIONS LEADS TO HALITOSIS - Dentino Asmara Putra; Ni Nengah Aderinaarta Pramudani; Armyawati; Wiwekowati (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2023)
Introduction. Halitosis is a dental and oral illness that is common in society. Steptococcus salivarius is the bacteria that causes halitosis. The purpose of this study was to determine whether lime peel extract toothpaste possesses any bioactive antibacterial properties against the strain of bacteria Streptococcus salivarius and can brighten teeth. Materials and Methods. The research method used was True Experimental Design. This research design used Post Test Only Control Design. Where there are three groups, namely the treatment group, positive control group, and negative control group. The data obtained will be tested statistically using the one-way ANOVA analysis with a confidence level of 95% and followed by the Least Significance test. Dental lightening research is carried out on teeth that have been extracted. Brush the teeth with lime peel paste for 7 days and do it 2 times a day. Tooth color was recorded before treatment and after treatment with shade guide Chromascop Ivoclar Vivedent. Result and Discussion. The results of this study showed that toothpaste with lime peel extract was able to inhibit the growth of Streptococcus salivarius bacteria. The respective concentrations of lime extract in toothpaste F0 to F4 are 0%, 2.5%, 5%, 7.5%, and 10%. K+ about using toothpaste on the market, with an average inhibition zone of F1 (8.7), F2 (9.86), F3 (11.58), F4 (13.4), K+ (19.65), and K- (0), so it can be stated that the more the extract content, the higher the inhibitory power for the growth of Streptococcus salivarius. Besides that, lime peel toothpaste can brighten teeth several levels Conclusion: Lime peel extract toothpaste is able to inhibit the growth of Streptococcus salivarius bacteria and is able to brighten teeth several levels.